Pemikiran Kaum Fundamentalis Muslim (Telaah terhadap Aktivitas Hizbut Tahrir) - M Dahlan M (Jurnal Adabiyah: Humanities and Islamic Studies, 2010)
Fundamentalism can be defined as a movement as well as a belief that strictly and literally hold religious principles. Such this movement was pionered by al-Khawarij Sect when Ali ruled al khilafah lslamiyah. Fundamentalism then was developed and adopted by lkhawan al-Muslimin in Egypt and continued by Hizbut Tahrir, a Freedom Party established by Taqiy al-Din al-Nabhani. Hizbut Tahrir regarded that khilafah is a very urgent system in building governance. In the other words, a very relevant system in managing the government is khilafah which had been ever implemented. by khulafa al-Rasyidin. Khilafah is not kingdom, nor imperium, nor federal but khilafah is a reflection of prophetic tradition that rules human life with syariat system.